2016
DOI: 10.1097/icu.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Current management of glaucoma and vascular occlusive disease

Abstract: Prompt diagnosis and management of glaucomas associated with vascular occlusive disease are required to allow for the best possible outcome. Novel anti-VEGF agents, particularly aflibercept, should be strongly considered in the management of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Although mainly approved for use in age-related macular degeneration and diabetic macular edema, anti-VEGF agents have been increasingly used in recent years to treat retinal ischemia. It has been shown to be beneficial in NVG when used alone14,15 and in conjunction with filtration surgery 1620. However, as mentioned, anti-VEGF treatment is currently not widely utilized (or available) for the management of NVG in Hong Kong due to its off-label use (for NVG) and high cost.…”
Section: Discussionmentioning
confidence: 99%
“…Although mainly approved for use in age-related macular degeneration and diabetic macular edema, anti-VEGF agents have been increasingly used in recent years to treat retinal ischemia. It has been shown to be beneficial in NVG when used alone14,15 and in conjunction with filtration surgery 1620. However, as mentioned, anti-VEGF treatment is currently not widely utilized (or available) for the management of NVG in Hong Kong due to its off-label use (for NVG) and high cost.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF was also present on immunostaining at the corneal surface and within the hemangioblastoma of an enucleated eye with neovascular glaucoma and VHL (Chen et al, 2015). Few small studies have shown that intravitreal anti-VEGF agents may lead to rapid regression of anterior chamber neovascularization due to all causes with a corresponding short-term decrease in IOP (Aref, 2016;Kim et al, 2015;Vasudev, Blair, Galasso, Kapur, & Vajaranant, 2009). However, long-term IOP reduction with anti-VEGF agents…”
Section: Pathophysiologymentioning
confidence: 99%
“…Few small studies have shown that intravitreal anti‐VEGF agents may lead to rapid regression of anterior chamber neovascularization due to all causes with a corresponding short‐term decrease in IOP (Aref, ; Kim et al, ; Vasudev, Blair, Galasso, Kapur, & Vajaranant, ). However, long‐term IOP reduction with anti‐VEGF agents has not yet been proven.…”
Section: Vhl Diseasementioning
confidence: 99%
“…2,8 Glokomun yarattığı optik sinir başı hasarının özellikle ileri glokom hastalarında fizyolojik üst sınır GİB değeri olan 21 mmHg'nin altına çekilmesi ile her zaman durdurulamadığı, dolayısıyla her hasta için PAAG progresyonunu durduran bir hedef GİB değeri belirlenmesi gerekliliği savunulmaktadır. 9,10 Yapılan birçok çalışmada hedef GİB değerine ulaşılabilmesi için tek bir ilacın yeterli olmadığı ve çoğunlukla çoklu ilaç kullanımının gerekli olduğu gösterilmiş-tir. [11][12][13] Sabit kombinasyon tedavileri, çoklu ilaç kullanımının neden olduğu birden fazla ilaçla çok sayıda damla damlatma ve tedavi aralıklarını takip etme gibi problemleri yok ederek hasta uyumunu kolaylaştırmaktadır.…”
Section: Bulgularunclassified